Human beta defensin-3 mediated activation of β-catenin during human respiratory syncytial virus infection: interaction of HBD3 with LDL receptor-related protein 5 - Pokharel, Swechha M.; Mohanty, Indira; Mariasoosai, Charles; Miura, Tanya A.; Maddison, Lisette A.; Natesan, Senthil; Bose, Santanu (Frontiers in Microbiology, 2023)
Respiratory Syncytial Virus (RSV) is a non-segmented negative-sense RNA virus belonging to the paramyxovirus family. RSV infects the respiratory tract to cause pneumonia and bronchiolitis in infants, elderly, and immunocompromised patients. Effective clinical therapeutic options and vaccines to combat RSV infection are still lacking. Therefore, to develop effective therapeutic interventions, it is imperative to understand virus-host interactions during RSV infection. Cytoplasmic stabilization of b-catenin protein results in activation of canonical Wingless (Wnt)/beta-catenin signaling pathway that culminates in transcriptional activation of various genes regulated by T-cell factor/lymphoid enhancer factor (TCF/LEF) transcription factors. This pathway is involved in various biological and physiological functions. Our study shows RSV infection of human lung epithelial A549 cells triggering beta-catenin protein stabilization and induction of beta-catenin mediated transcriptional activity. Functionally, the activated beta-catenin pathway promoted a pro-inflammatory response during RSV infection of lung epithelial cells. Studies with beta-catenin inhibitors and A549 cells lacking optimal beta-catenin activity demonstrated a significant loss of pro-inflammatory chemokine interleukin-8 (IL-8) release from RSV-infected cells. Mechanistically, our studies revealed a role of extracellular human beta defensin-3 (HBD3) in interacting with cell surface Wnt receptor LDL receptor-related protein-5 (LRP5) to activate the non-canonical Wnt independent beta-catenin pathway during RSV infection. We showed gene expression and release of HBD3 from RSV-infected cells, and silencing of HBD3 expression resulted in reduced stabilization of beta-catenin protein during RSV infection. Furthermore, we observed the binding of extracellular HBD3 with cell surface localized LRP5 protein, and our in silico and protein-protein interaction studies have highlighted a direct interaction of HBD3 with LRP5. Thus, our studies have identified the beta-catenin pathway as a key regulator of pro-inflammatory response during RSV infection of human lung epithelial cells. This pathway was induced during RSV infection via a non-canonical Wnt-independent mechanism involving paracrine/autocrine action of extracellular HBD3 activating cell surface Wnt receptor complex by directly interacting with the LRP5 receptor